2010
DOI: 10.1111/j.1365-2559.2010.03660.x
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular large B cell lymphoma with hepatic portal vein, splenic vein and mesenteric vein tumour embolism

Abstract: 1. Mutter GL, Baak JPA, Crum CP, Richart RM, Ferenczy A, Farquir W. Endometrial precancer diagnosis by histopathology, clonal analysis and computerized morphometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
(9 reference statements)
1
8
0
Order By: Relevance
“…As expected, no tumor cells were seen in this area. Similar findings were reported by Yasuda et al (16), who described multiple thrombotic lesions in the hepatic vessels and splenic vein at autopsy; these lesions were seen on the CT studies performed in the antemortem period and confirmed in the postmortem period. These findings suggest that, if a diagnosis of hepatic IVL is suspected when employing multiple imaging modalities, a tumor lesion-specific liver biopsy should be performed to confirm the presence of sinusoidal invasion, because a random liver biopsy may fail to detect tumor cells if it is performed in peripheral lesions (as evidenced in our case).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As expected, no tumor cells were seen in this area. Similar findings were reported by Yasuda et al (16), who described multiple thrombotic lesions in the hepatic vessels and splenic vein at autopsy; these lesions were seen on the CT studies performed in the antemortem period and confirmed in the postmortem period. These findings suggest that, if a diagnosis of hepatic IVL is suspected when employing multiple imaging modalities, a tumor lesion-specific liver biopsy should be performed to confirm the presence of sinusoidal invasion, because a random liver biopsy may fail to detect tumor cells if it is performed in peripheral lesions (as evidenced in our case).…”
Section: Discussionsupporting
confidence: 90%
“…The patient was successfully treated with chemotherapy following the histological diagnosis of hepatic IVL (13). However, due to the difficulty in confirming the suspicion of liver invasion using imaging studies and biopsy methods, to date the number of cases involving the liver diagnosed in the antemortem period is lower than that observed in the postmortem period (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) (Table). Our literature review of hepatic IVL cases diagnosed using imaging studies of the liver revealed that six of 10 cases were diagnosed at autopsy, and no specific findings were observed in the conventional CT studies (Table).…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node inflammatory proliferation is considered with multiple bilateral neck and mediastinum lymph nodes enlargement. This indicates the occlusion of lymphoma cells in the vasculature, causing thrombosis and multiple system dysfunctions [9]. The enlarged lymph nodes may block drainage of fluid that lubricates the pelvic cavity, causing effusion accumulations and symptoms such as lower limb edema, pelvic effusion, and anorexia.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 3 cases of IVLBCL-associated acute abdomen have been reported. In 2 of the 3 cases, the occlusion was observed in the mesenteric vein [13,14]; in the third case, the hepatic portal, splenic, and mesenteric veins were involved [15]. Therefore, our case showed a novel manifestation of IVLBCL, with simultaneous thrombosis of both the mesenteric artery and vein.…”
Section: Discussionmentioning
confidence: 98%